Edukasi dan Pendampingan Permasalahan Kekerasan Seksual pada Siswa di Lingkungan Sekolah Menengah Atas - Meilantika, Ayu Diana; Rizky, Ayu; Masdah, Siti (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The problems found show that there are still some students who have experienced sexual violence committed by those closest to them, causing them to drop out of school due to embarrassment with their school friends. This is certainly a problem that must be addressed and overcome, if left unchecked it will have an impact on their psychological and mental state. So the purpose of this service is to provide education in the form of socialization about sexual violence to students at Bina Utama High School. This activity was carried out using the lecture method in the form of presentations and evaluated using questionnaires given before and after the activity. The results showed that socialization and mentoring activities to students about sexual violence, there was a significant increase in knowledge. Socialization and mentoring are effective in increasing knowledge and changing students' attitudes at Bina Utama Pontianak High School. Therefore, it is recommended that mentoring education on sexual violence in adolescents needs to be improved so that the younger generation is protected from sexual violence.